Shaping Future GATS Rules for Trade in Services - Mattoo, Aaditya (World Bank, Washington, DC, 2014)
The new round of negotiations has begun with a mechanical sense of "since we said we would, therefore we must," says the author. To make the General Agreement on Trade in Services (GATS) more effective ay liberalization, the author suggests improving the agreement's rules, countries' specific commitments, and the negotiating methodology: 1) Wasteful regulations, and entry restrictions pervade trade in services. Unlike the GATT, the GATS has created no hierarchy of instruments of protection. It may be possible to create a legal presumption in favor of instruments (such as fiscal measures) that provide protection more efficiently. 2) Many countries have taken advantage of the GATS to create a more secure trading environment, by making legally binding commitments to market access. The credibility of reform would increase with wider commitments to maintain current levels of openness, or to increase access in the future. 3) Multilateral rules on domestic regulations can help promote, and consolidate domestic regulatory reform, even when the rules are designed primarily to prevent the erosion of market access for foreign providers. The pro-competitive principles developed for basic communications, could be extended to other network-based services sectors, such as transport (terminals and infrastructure), and energy services (distribution networks). The "necessity test" instituted for accounting services, could be applied to instruments in other sectors (so that doctors judged competent in one jurisdiction, wouldn't have to be retrained for another, for example). 4) Anticompetitive practices that fall outside the jurisdiction of national competition law, may be important in such sectors as maritime, air transport, and communications services. Strengthened multilateral rules are needed to reassure small countries with weak enforcement capacity, that the gains from liberalization will not be appropriated by international cartels. 5) Explicit departures from the most-favored-nation rule matter most in such sectors as maritime transport, audiovisual services, and air transport services - which have been excluded from key GATS disciplines. Implicit discrimination can be prevented by developing rules to ensure the non-discriminatory allocation of quotas, and maintaining the desirable openness of the GATS provision on mutual recognition agreements. 6) Reciprocity must play a greater role in negotiations, if the GATS is to advance liberalization beyond measures taken independently.